2022
DOI: 10.1038/s41420-022-01126-x
|View full text |Cite
|
Sign up to set email alerts
|

RBCK1 promotes hepatocellular carcinoma metastasis and growth by stabilizing RNF31

Abstract: RNF31 (HOIP), RBCK1 (HOIL-1L), and SHARPIN are subunits of the linear ubiquitin chain assembly complex. Their function and specific molecular mechanisms in hepatocellular carcinoma (HCC) have not been reported previously. Here, we investigated the role of RNF31 and RBCK1 in HCC. We showed that RNF31 and RBCK1 were overexpressed in HCC and that upregulation of RNF31 and RBCK1 indicated poor clinical outcomes in patients with HCC. RNF31 overexpression was significantly associated with more satellite foci and vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Because RNF31 and RBCK1 are both essential components of the LUBAC, we suspected that the stabilization of RNF31 by RBCK1 could increase LUBAC formation and subsequently trigger enhanced NF-κB activation via linear ubiquitination. Consistent with this, Chen et al showed that gliotoxin, an inhibitor of LUBAC activity, has inhibitory effects on HCC cell lines 25 . However, they did not clarify whether the inhibitory effect of gliotoxin was due to LUBAC or NF-κB activity, as gliotoxin itself has cytotoxicity 23 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Because RNF31 and RBCK1 are both essential components of the LUBAC, we suspected that the stabilization of RNF31 by RBCK1 could increase LUBAC formation and subsequently trigger enhanced NF-κB activation via linear ubiquitination. Consistent with this, Chen et al showed that gliotoxin, an inhibitor of LUBAC activity, has inhibitory effects on HCC cell lines 25 . However, they did not clarify whether the inhibitory effect of gliotoxin was due to LUBAC or NF-κB activity, as gliotoxin itself has cytotoxicity 23 .…”
Section: Discussionmentioning
confidence: 68%
“…However, in our cohort, RNF31 expression was not correlated with viral hepatitis or liver cirrhosis. Chen et al also reported that there was no correlation between RNF31 expression and HBV or cirrhosis 25 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the previous studies, it had been reported that the expression of RBCK1 and Sharpin was upregulated in tumor tissues [29,30], and exerted oncogenic functions by stabilizing the expression RNF31 and promoting the transactivation of Versican expression; however, it was independent of their M1-Ubi activity. Thus, a more comprehensive study is needed on the potential functions of M1-Ubi and LUBAC components in HCC, especially in HBV-associated HCC.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, quite a few E3 ubiquitin ligases have exhibited abnormal expression in tumors, making them valuable diagnostic markers and drug targets [32]. Previous studies have revealed that publicly-available databases and in vitro analysis have determined that mRNA expression of RBCK1 in HCC cells and tissues was significantly higher than those of normal counterparts [30,33]. For factors upregulating the expression of RBCK1, Queisser MA et al .…”
Section: Discussionmentioning
confidence: 99%